2013
DOI: 10.1249/jsr.0b013e31829a74fd
|View full text |Cite
|
Sign up to set email alerts
|

Brain Health and Exercise in Older Adults

Abstract: Identifying feasible and effective interventions aimed at mitigating the effects of cognitive decline in older adults is currently a high priority for researchers, clinicians, and policy makers. Evidence suggests that exercise and cognitive training benefit cognitive health in older adults; however, a preferred modality has to be endorsed yet by the scientific community. The purpose of this review is to discuss and critically examine the current state of knowledge concerning the effects of aerobic, resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 64 publications
3
44
0
2
Order By: Relevance
“…This is supported by observational studies with longer follow-up that have found these effects remain even after excluding participants who progress to dementia within a few years of assessment of CA and PA [4]. There is also growing support from separate CA [14, 30] and PA [31, 32] interventions showing improvements in cognitive functioning.…”
Section: Discussionmentioning
confidence: 93%
“…This is supported by observational studies with longer follow-up that have found these effects remain even after excluding participants who progress to dementia within a few years of assessment of CA and PA [4]. There is also growing support from separate CA [14, 30] and PA [31, 32] interventions showing improvements in cognitive functioning.…”
Section: Discussionmentioning
confidence: 93%
“…First, can modification of risk factors in the general population, such as diabetes, hypertension, smoking, obesity, less physical activity, delay cognitive decline and dementia either by modifying the development of brain amyloid, less neurodegeneration, and brain reserve [8588]? A recent report from the Alzheimer’s Association stated there was strong evidence from a population perspective that regular physical activity and management of cardiovascular risk factors reduced the risk of cognitive decline and may also reduce the risk of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training is especially valuable among the aged as this mode of exercise has been found to be successful in treating or preventing chronic health conditions associated with senescence including sarcopenia (age-related loss of muscle mass), osteoporosis, insulin resistance, incidence of accidental falls, bone fracture, and even cognitive decline (Anton et al, 2013; Cederholm et al, 2013; Engelke et al, 2006; Gregory et al, 2013; Liu-Ambrose and Donaldson, 2009; Visser, 2011; Westcott, 2012). Resistance training typically results in positive adaptations of the neuromuscular system including myofibers and neuromuscular junctions (NMJs) which link the motor nervous system with skeletal muscles that are activated by those motor neurons (Andersen and Aagaard, 2010; Deschenes et al, 2000; Folland and Williams, 2007).…”
Section: Introductionmentioning
confidence: 99%